Pertanggungjawaban Pidana Korporasi dalam Tindak Pidana Pencucian Uang di Indonesia: Penguatan Kerangka Normatif dan Penegakan Hukum - Apriany Marwan, Wiwiek (Sawerigading Law Journal, 2024)
Corporate crime, particularly in the form of money laundering, increasingly challenges the integrity of the legal system and the economy by exploiting legal structures, the complexity of financial transactions, and weaknesses in corporate governance. This article provides a normative legal analysis of the construction of corporate criminal liability in money laundering, the main problems in law enforcement, and the direction of strengthening criminal law policy. The method used combines a legislative and conceptual approach by interpreting norms, constructing the doctrine of corporate criminal liability, and reviewing research findings related to the practices of evidence and asset recovery. The results of the study show that the positive legal framework actually provides a basis for prosecuting corporations and their controllers, including through fines, asset forfeiture, business activity restrictions, and other additional sanctions. However, law enforcement practices still face various obstacles, including difficulties in compiling comprehensive indictments, limited capacity for asset tracing and confiscation, weak coordination between institutions, suboptimal disclosure of beneficial owners, and an underdeveloped culture of internal compliance. This article recommends refining the corporate criminal liability model, reorienting the design of sanctions to focus on deterrence and recovery of losses, strengthening the asset confiscation regime, optimizing ownership transparency, and increasing the capacity and synergy between law enforcement agencies and business actors so that the regime for combating corporate money laundering is more effective and sustainable. The theoretical and practical contributions of this paper lie in mapping implementation gaps and offering policy reforms that are more responsive to the nature of modern corporate crime.